STRATEGI PENGEMBANGAN TERMINAL TIPE A SIWAGILEMBA KECAMATAN POSO KOTA SELATAN DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN POSO - Siswanto, Joko (Katalogis, 2013)
The purpose of this research to know and analyze the increase strategy of retribution received by terminal in order to increase the authority income (PAD) in Poso regency. The population in this research that are terminal official, public transport driver in terminal area of type A Siwagilemba of South Poso District, transport service provider and some functionaries that handle and know about the terminal case, the sample which is taken from the population are 70 people thatâ€™s considered as representatives. The sampling method is used namely purposive sampling that is sample determination technique with particular consideration, in this technique there is not all the population has opportunity as the sample. The collection of primary and secondary data have been done with interview, focus group discussion (FGD), questionnaire and documentation. The realization of contribution terminal has been analyzed by formula P = (Xi/X) x 100 %. The contribution in 2012 for authority original income as 0,38%. The opinion of respondent and informant is analyzed by SWOT. The technical and analysis of data is usedÂ  SWOT method (Strength, Weakness, Opportunities and Threats). In SWOT matrix is known internal factor (Strength and Weakness) and external factor (Opportunities and Threats) there is in Terminal Type A Siwagilemba of South Poso district. Based on account coordinate unit of SWOT is known that the organization position of terminal unit Type Siwagilemba in South Poso District of Poso Regency, there is lied on quadrant I so that the strategy must be used is SO (Strength-Opportunity) that are: (1) to allocate in income budget and educational program and technique training in order to increase officer professional LLAJ. (2) Optimize discipline degree and authority of official LLAJ, to work the orderly for the main facility benefit and supporting in terminal. (3) to useful of amount and the level discipline of LLAJ officers to supervise and control the public transport for daily and operate the low obey with instance related, (4) to useful of the strategy terminal position, with develop the South Poso district as growth centre, and (5) to use amount of LLAJ officers to implement the socialization or implementation operational regulation of terminal for all sides.